Tyrosine Phosphorylation Based Homo-dimerization of Arabidopsis RACK1A Proteins Regulates Oxidative Stress Signaling Pathways in Yeast - Sabila, Mercy; Kundu, Nabanita; Smalls, Deana; Ullah, Hemayet (Frontiers in Plant Science, 2016)
Scaffold proteins are known as important cellular regulators that can interact with multiple proteins to modulate diverse signal transduction pathways. RACK1 (Receptor for Activated C Kinase 1) is a WD-40 type scaffold protein, conserved in eukaryotes, from Chlamydymonas to plants and humans, plays regulatory roles in diverse signal transduction and stress response pathways. RACK1 in humans has been implicated in myriads of neuropathological diseases including Alzheimer and alcohol addictions. Model plant Arabidopsis thaliana genome maintains three different RACK1 genes termed RACK1A, RACK1B, and RACK1C with a very high (85–93%) sequence identity among them. Loss of function mutation in Arabidopsis indicates that RACK1 proteins regulate diverse environmental stress signaling pathways including drought and salt stress resistance pathway. Recently deduced crystal structure of Arabidopsis RACK1A- very first among all of the RACK1 proteins, indicates that it can potentially be regulated by post-translational modifications, like tyrosine phosphorylations and sumoylation at key residues. Here we show evidence that RACK1A proteins, depending on diverse environmental stresses, are tyrosine phosphorylated. Utilizing site-directed mutagenesis of key tyrosine residues, it is found that tyrosine phosphorylation can potentially dictate the homo-dimerization of RACK1A proteins. The homo-dimerized RACK1A proteins play a role in providing UV-B induced oxidative stress resistance. It is proposed that RACK1A proteins ability to function as scaffold protein may potentially be regulated by the homo-dimerized RACK1A proteins to mediate diverse stress signaling pathways.